SPECIFICITY OF CONCERTMASTER’S WORK IN THE PROCESS OF DISTANCE LEARNING - Харченко, Ю.Т. (SWorldJournal, 2022)
The abstracts consider the professional activity of the concertmaster of the institution of higher education in terms of the use of information technology. It is noted that the use of information technology at the preparatory and rehearsal stages of the c